The Possible Incoming Runoff Under Extreme Rainfall Event in the Fenhe River Basin - Jian, Shengqi; Yin, Changyan; Wang, Yafei; Yu, Xin; Li, Yong (Frontiers in Environmental Science, 2022)
Prediction of runoff is of great significance for the sustainable utilization of water resources and flood control and disaster reduction in the basin. In this study, a method for predicting the runoff caused by extreme sub-rainfall events was constructed based on the identification of extreme rainfall events, Mann–Kendall Test, R/S analysis, and regression analysis. The method was applied to the Jingle sub-basin, and the results showed that the extreme precipitation in this basin will maintain a slight rising trend in the future, assuming that the climate and underlying conditions remain the same as they were in the current scenario. There is a more stable correlational relationship between rainfall characteristic factors and runoff in extreme rainfall events. The extreme precipitation of 1–5 consecutive days under the 100a return period designed by the hydrological frequency method is 38.74, 60.01, 66.00, 71.44, and 73.69 mm, respectively, and the possible runoff predicted by the four empirical formulas is 1295−2495, 2108−4935, 2408−5801, and 3051−7062 × 104 m3, respectively. The rainfall designed by the hydrological frequency combination method is 203.64 mm, and the possible runoff predicted by the four empirical formulas is 2.8−5.3 × 108 m3. This study can provide a new reference for predicting the possible incoming runoff under extreme sub-rainfall events.